The Role of Inflammation in Diabetes: Current Concepts and Future Perspectives - Sotirios Tsalamandris (Radcliffe Medical Media, 2019)
Diabetes is a complex metabolic disorder affecting the glucose status of the human body. Chronic hyperglycaemia related to diabetes is associated with end organ failure. The clinical relationship between diabetes and atherosclerotic cardiovascular disease is well established. This makes therapeutic approaches that simultaneously target diabetes and atherosclerotic disease an attractive area for research. The majority of people with diabetes fall into two broad pathogenetic categories, type 1 or type 2 diabetes. The role of obesity, adipose tissue, gut microbiota and pancreatic beta cell function in diabetes are under intensive scrutiny with several clinical trials to have been completed while more are in development. The emerging role of inflammation in both type 1 and type 2 diabetes (T1D and T1D) pathophysiology and associated metabolic disorders, has generated increasing interest in targeting inflammation to improve prevention and control of the disease. After an extensive review of the possible mechanisms that drive the metabolic pattern in T1D and T2D and the inflammatory pathways that are involved, it becomes ever clearer that future research should focus on a model of combined suppression for various inflammatory response pathways.